Premium auctions and risk preferences: an experimental study [dataset] - Brunner, Christoph; Hu, Audrey Xianhua; Oechssler, Joerg (Universität, 2023)
In premium auctions, the highest losing bidder receives a reward from the seller. This paper studies the private value English premium auction (EPA...